Perlindungan Hukum Terhadap Kesempatan Kerja Bagi Masyarakat Lokal Di Kota Cilegon - Fuqoha Fuqoha (Jurnal Wawasan Yuridika, 2018)
Legal protection of employement opportunities and welfare is the responsibility of the state. In the concept of regional autonomy it becomes the joint responsibility between the central and local governments to create opportunities and employment opportunities to provide welfare for the community, especially regional or local people. The form of legal protection afforded to the public may be a persuasive and repressive legal protection. Based on the state constitution until legislation has been regulated and on employment opportunities to the local people. This means that the legal protection of employment opportunities has been persuasive done by central and local governments. However, repressive legal protection for local people is not yet fully implemented, resulting in high numbers of job seekers for regional or local people.